Implikasi Penafian Peran Notaris dalam Eksistensi Perseroan Perorangan - Widiyanti, Ida; Putrijanti, Aju (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2024)
ABSTRACTThe existence of individual companies after the promulgation of the Job Creation Act has the government's policies in facilitating the formation of companies for UMK. This convenience is company can be done electronically, without the need notary role. The existence of Company legalized without Notary. This research purpose to understand and comprehensively analyze the role of Notary in the existence of individual company. Researchers use normative juridical methods and use an approach in literature. The conclusion is individual company that is formed without involving the role of notary will lead to responsibilities must be borne by the founders themselves. Notaries have’t the authority to form companies, especially for UMK. The existence of electronic incorporation statement is considered sufficient for the legality company.Keyword: Role of Notary; Existence; Private CompanyABSTRAKKeberadaan Perseroan Perorangan pasca diundangkannya UU Cipta Kerja adalah kebijakan pemerintah mempermudah pembentukan perseroan bagi UMK. Kemudahan tersebut yaitu pembentukan perseroan dapat dilakukan secara elektronik, tanpa membutuhkan peran Notaris. Eksistensi Perseroan dilegalkan tanpa adanya akta Notaris. Penelitian ini bertujuan memahami dan menganalisia secara komprehensif tentang peran Notaris dalam eksistensi perseroan perorangan. Peneliti menggunakan metode yuridis normatif dan metode pendekatan kepustakaan. Kesimpulan penelitian ini adalah perseroan perorangan yang dibentuk tanpa melibatkan peran Notaris akan menimbulkan tanggungjawab yang harus ditanggung sendiri oleh pendiri. Notaris tidak mempunyai kewenangan dalam pembentukan perseroan khususnya untuk UMK semenjak diundangkannya Undang-Undang Cipta Kerja. Keberadaan pernyataan pendirian elektronik dianggap sudah cukup untuk legalitas perseroan.Kata Kunci: Peran Notaris; Eksistensi; Perseroan Perorangan